COMPASS IN THE HOUSEHOLD: OBSERVING THE LEVEL OF UNDERSTANDING OF ISLAMIC FAMILY LAW IN THE LIFE OF GRESIK URBAN MUSLIMS - Rohman, M. Imdadur; Mahmudah, Nurul; Al kautsar, Muhammad Syakir; Orwela, Citra (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2024)
In an increasingly dynamic and modern urban context, understanding Islamic family law has become essential for Muslim individuals. This article aims to evaluate the level of understanding of the Gresik urban community about Islamic family law and how this law can be applied in everyday life. This study used a quantitative approach by distributing questionnaires to 56 respondents selected purposively from the Muslim community population in RT RW Gresik City, East Java. The research results show that in Gresik, the majority of respondents (76-100%) have a good understanding of Islamic family law, which is indicated by positive responses to the statements in the questionnaire, even though there are several obstacles faced by the head of the family such as inability to apply it practically due to diverse environmental conditions in society. This research contributes to understanding the perspective of urban Muslim communities towards Islamic family law and formulating policies and strategies appropriate to this era.